Nurse‐led one stop hematuria clinic: Outcomes from 2, 714 patients. Issue 6 (12th June 2021) - Madaan, Anika; Kuusk, Teele; Hamdoon, Musaab; Elliott, Angela; Pearce, Dianne; Madaan, Sanjeev
Abstract: Objectives: Objective of this study is to report the results of nurse led hematuria clinic service outcome of 2, 714 patients. Subjects and methods: We conducted a retrospective, single center review of 2714 patients with visible and nonvisible hematuria managed by a well‐trained nurse specialist in a rapid access clinic (RAC) between 2014 and 2020. All patients received a full review, flexible cystoscopy performed by a nurse, and ultrasound of urinary tracts. After investigations, patients were reassured and discharged or referred for rigid cystoscopy, TURBT, and CT urography. Results: In total, 2714 patients attended the RAC between October 2014 and March 2020. Of these, 1684 (62%) were males and 1030 (38%) females. The median age of patients was 68.3 (IQR 58‐79). Of the 1030 females, 500 (48.5%) presented with nonvisible hematuria (NVH), and 530 (51.5%) presented with visible hematuria (VH). The median age was 66 (IQR 56‐76). The number of females diagnosed with any form of malignancy was 72 (7% of all females). Of the 1684 males, 288 (17.1%) presented with NVH, and 1396 (82.9%) presented with VH. The median age was 72 (IQR 59‐81). The number of males diagnosed with some form of malignancy was 258 (15.3% of all males). Overall, 1926 patients presented with VH and 788 patients presented with NVH. After investigations, 290 patients (15.1%) with VH and 40 (5.1%) patients with NVH had some form of malignancy. The highest number of malignancies found in VH was bladder cancer (n = 222, 11.5%), followed by prostate (n = 28, 1%), renal (n = 23, 0.8%), UT urothelial (n = 17, 0.6%), gynaecological (n = 7, 0.3%), and gastrointestinal (n = 5, 0.2%) cancer. The highest number of pathologies found in NVH was infection (n = 44, 5.6%). Cancer detection rate for symptomatic NVH was more than double that of asymptomatic NVH, 6.5% versus 3.1%, respectively. Conclusion: Overall, 15.1% with VH and 5.1% with NVH present with malignancy. Nurse‐led rapid access hematuria clinic and flexible cystoscopy investigation by trained nurse is safe and feasible.